Requiem for Neil Smith: a retrospective of the author's thought on gentrification from the lens of critical geography - Mendes, Luís (2019)
This article aims to make a retrospective of the several theses that for decades characterized the work of Neil Smith on gentrification and the agents and processes inherent in this process. It is based on the discussion and reflection on the several perspectives of the Marxist paradigm of geography and its impact on the concepts and methodology used by Smith, from the late 1970s until the recent end of his academic career, to understand and analyze the process of gentrification as urban restructuring, within the theoretical and methodological framework of Critical Geography.